2010
DOI: 10.1007/s00405-010-1324-x
|View full text |Cite
|
Sign up to set email alerts
|

Staged-surgery with permanent pathology for the management of high-risk nonmelanoma skin cancer of the nose

Abstract: The objective of the study was to investigate the effect of staged-surgery with permanent pathology on tumour recurrence of high-risk nonmelanoma skin cancers (NMSCs) of the nose and to determine the factors associated with subclinical spread and deep-margin involvement. Twenty-one patients who underwent staged-surgery with permanent pathology for high-risk NMSCs of the nose between 2007 and 2008 were prospectively followed-up for tumour recurrence. The incidence of tumour recurrence after staged-surgery with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition, in some previous studies, SEPMC has been performed in either low- and high-risk BCCs or specific areas such as the nose or periorbital area. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in some previous studies, SEPMC has been performed in either low- and high-risk BCCs or specific areas such as the nose or periorbital area. 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Staged excision with pathologic margin control (SEPMC) is a simple and accessible procedure with a high cure rate that is suggested for the treatment of special types of BCC or for special sites such as periorbital or nasal areas. 6 , 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…It is known that the presence of vital structures in the head and neck region and the difficulty of identifying tumor boundaries due to sun exposure require careful consideration of surgical margins in skin cancers. In relation to this clinical challenge, we have reported there liable role of "staged surgery" for the reduction of local recurrences in high-risk non-melanoma skin cancers [19] . Furthermore, Moyer et al concluded that staged tumor resection was an effective and useful technique and decreased local recurrences in cutaneous malignant melanoma of the head and neck [20] .…”
Section: What Is the Surgical Margin For Cutaneous Malignant Melanomamentioning
confidence: 99%
“…The tumorous processes of the skin increase patient worries and thus addressing frequencies by primary care services, dermatology, plastic surgery. Typically, concern relates to the patient on the cosmetic appearance and on the malignant potential of the lesion [3,4]. Knowing the most common forms of benign and malignant skin tumours is crucial for a proper evaluation and therapeutic management.…”
Section: Introductionmentioning
confidence: 99%